Nontraumatic Exertional Fatalities in Football Players, Part 1: Epidemiology and Effectiveness of National Collegiate Athletic Association Bylaws. Issue 8 (19th August 2020) - Boden, Barry P.; Fine, Ken M.; Breit, Ilan; Lentz, Wendee; Anderson, Scott A.
Background: Football has the highest number of nontraumatic fatalities of any sport in the United States. Purpose: To compare the incidence of nontraumatic fatalities with that of traumatic fatalities, describe the epidemiology of nontraumatic fatalities in high school (HS) and college football players, and determine the effectiveness of National Collegiate Athletic Association (NCAA) policies to reduce exertional heat stroke (EHS) and exertional sickling (ES) with sickle cell trait (SCT) fatalities in athletes. Study Design: Descriptive epidemiology study. Methods: We retrospectively reviewed 20 academic years (1998-2018) of HS and college nontraumatic fatalities in football players using the National Registry of Catastrophic Sports Injuries (NRCSI). EHS and ES with SCT fatality rates were compared before and after the implementation of the NCAA football out-of-season model (bylaw 17.10.2.4 [2003]) and NCAA Division I SCT screening (bylaw 17.1.5.1 [2010]), respectively. Additionally, we compiled incidence trends for HS and college traumatic and nontraumatic fatalities in football players for the years 1960 through 2018 based on NRCSI data and previously published reports. Results: The risk (odds ratio) of traumatic fatalities in football players in the 2010s was 0.19 (95% CI, 0.13-0.26; P < .0001) lower in HS and 0.29 (95% CI, 0.29-0.72; P = .0078) lower in college compared with that in the 1960s. In contrast, the risk of nontraumatic fatalities in football players in the 2010s was 0.7 (95% CI, 0.50-0.98; P = .0353) in HS and 0.9 (95% CI, 0.46-1.72; P = .7413) in college compared with that in the 1960s. Since 2000, the risk of nontraumatic fatalities has been 1.89 (95% CI, 1.42-2.51; P < .001) and 4.22 (95% CI, 2.04-8.73; P < .001) higher than the risk of traumatic fatalities at the HS and college levels, respectively. During the 20 years studied, there were 187 nontraumatic fatalities (average, 9.4 per year). The causes of death were sudden cardiac arrest (57.7%), EHS (23.6%), ES with SCT (12.1%), asthma (4.9%), and hyponatremia (1.6%). The risk of a nontraumatic fatality was 4.1 (95% CI, 2.8-5.9; P < .0001) higher in NCAA compared with HS athletes. There was no difference in the risk of an EHS fatality in NCAA athletes (0.86 [95% CI, 0.17-4.25]; P = .85) after implementation in 2003 of the NCAA football out-of-season model. The risk of an ES with SCT fatality in Division I athletes was significantly lower after the 2010 NCAA SCT screening bylaw was implemented (0.12 [95% CI, 0.02-0.95]; P = .04). Conclusion: Since the 1960s, the risk of nontraumatic fatalities has declined minimally compared with the reduction in the risk of traumatic fatalities. Current HS and college nontraumatic fatality rates are significantly higher than rates of traumatic fatalities. The 2003 NCAA out-of-season model has failed to significantly reduce EHS fatalities. The 2010 NCAA SCT screening bylaw has effectively prevented ES with SCT fatalities in NCAA Division I football.